Perception of small medium and enterprises towards halal food supply chain in Malaysia - Bakri, Mohammed Hariri; Rahim Azmi, Fadhlur; Abdullah, Abu; Musa, Haslinda (IAEME Publication, 2018)
The purpose of this paper is to investigate the perception of small medium and enterprises (SMEs) that motivates to adopt halal food supply chain (HFSC) in their business. Data were collected through a survey responded 183 out of 410 potential respondents from Halal Industry Development Corporation (HDC) directory website. Reliability analyses were applied to test the internal consistency of survey instrument. Moreover, regression analysis was applied to determine the predicted factors of SME’s perception towards the adoption of HFSC. Results showed that top management, organizational readiness, halal integrity, halal awareness and expected business benefits showed significantly positive relationship towards the adoption of HFSC. Furthermore, halal integrity showed the strongest factors towards its adoption. However, the understanding practice of halal showed insignificant towards it adoption. The findings of the present study have several relevant contributions towards food industry which adopt HFSC. In order to adopt HFSC, food manufacturers must embody Islamic culture to ensure the halalness of the products. The aspects of halal integrity will be integrated into the production realms to fulfil the global standard’s needs.